Augmented Reality for Solar System Learning - Herrera Salazar, José Luis (2020)
The learning process has difficulties due to an excess of theory and low use of teaching materials. Augmented reality in education would provide a new approach to learning, bringing virtual objects into the real world, improving interaction, increasing interest and improving the understanding of the topic to be taught. The research aimed at measuring the level of influence of the use of a mobile application with augmented reality in the learning of the solar system; the design was quasi-experimental with a control group and an experimental group, each of them consisted of 27 students. It was possible to demonstrate a significant improvement in the values of the indicators of the Post-test with respect to those of the Pre-test, which allows us to conclude that the augmented reality application significantly influences the learning of the solar system in primary school students.